Primary Gallbladder Lymphoma in a Male Patient with No Risk Factors Detected Incidentally by CT Colonography - Monil Karia; Grigorios Mitsopoulos; Ketan Patel; Akkib Rafique; Hemant Sheth (Case Reports in Surgery)
Primary gallbladder lymphoma, although rare, usually presents in females with symptoms mimicking cholecystitis. We present a rare case of primary gallbladder in an 81-year-old male with no risk factors whose only symptom was weight loss. Routine blood tests including liver function tests were unremarkable. A CT colonography was carried out to exclude colonic malignancy. Unilateral gallbladder wall thickening and lymphadenopathy were incidentally detected and confirmed by ultrasound and a decision for the patient to undergo laparoscopic cholecystectomy and intraoperative cholangiogram was made. Histology confirmed extranodal marginal zone lymphoma with follow-up staging and biopsy of the bone marrow not demonstrating spread. Cholecystectomy was therefore deemed curative and no adjuvant therapy was necessary. Thickening of the gallbladder wall on any imaging with or without symptoms should not be ignored or assumed to be cholecystitis, even in males with no risk factors. In these patients urgent cholecystectomy with intraoperative cholangiogram is indicated with histology and haematology follow-up.